José Carlos Mariátegui: When pedagogy leads to neocolonialism; reflections on education - Ward, Thomas (2020)
The awareness of the «surviving colonialism» of the Peruvian society is generally recognized in the thought of José Carlos Mariátegui. In order to annihilate this, he opposed the Spanish culture that prevailed in the society and sought other models, including Marxism. Another predisposition in his theories, uncommonlyinterpreted, is found in the positivism brought by the proposals of Manuel V. Villarán, Rector of The National University of San Marcos (Universidad Nacional Mayor de San Marcos), whose pedagogy was characterized by two elements: a rejection of the literate affinity of the Spanish pedagogy and a proposal focused on an education encouraging commerce (professions). This study will analyze the section of Mariátegui’s Seven Interpretive Essays on Peruvian Reality (Siete ensayos de interpretación de la literatura peruana) that is related to the essays «The liberal professions in Peru» («Las profesiones liberales en el Perú») and «The economic factor in national education» («El factor económico en la educación nacional») by Manuel Villarán. It will be studied how Marxism and positivism are combined in Mariátegui’s pedagogical proposals, showing how, inadvertently, Mariátegui’s anti-colonialism leaves room for neocolonialism.